The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/2279-042x.132704
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of pre- and post-menopausal breast cancer: Risk factors, presentation, characteristics and management

Abstract: Objective:Breast cancer is the most common female cancer worldwide and is the second most commonly diagnosed cancer in Indian women. This study evaluates the differences between pre- and post-menopausal breast cancer women regarding risk factors, nature of disease presentation, tumor characteristics, and management.Methods:This is a prospective observational study, conducted in the Oncology Department of St. Ann's Cancer Hospital, for a period of 6 months from January to August 2012. Data on basic demography, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
76
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 12 publications
11
76
0
3
Order By: Relevance
“…Null parity was associated with an overall increased risk of BC. Contradictory to those studies, we have found that many women presented with BC despite of high parity, which agrees with a previous study conducted on Indian women by Surakasula et al [24], who showed similar findings. Post-menopausal status showed the highest frequency among BC women in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Null parity was associated with an overall increased risk of BC. Contradictory to those studies, we have found that many women presented with BC despite of high parity, which agrees with a previous study conducted on Indian women by Surakasula et al [24], who showed similar findings. Post-menopausal status showed the highest frequency among BC women in this study.…”
Section: Discussionsupporting
confidence: 81%
“…similar findings are noticed in the studies conducted by other authors [4][5][6]. Similar findings were notice in studies conducted elsewhere [11][12]. The probable reason for such observation may be linked to the established fact that breast feeding reduces the risk of breast cancer.…”
Section: Methodssupporting
confidence: 81%
“…amounting to about 67%in contrast to women who attain menarche after 13 years of age(34%). Similar findings are noticed in other studies [11][12] and hormonal reasons are attributed for the same. It is observed from the table no.6 that the incidence of breast cancer is less who are highly educated that whole has no or formal primary education.…”
Section: Methodssupporting
confidence: 81%
“…Higher proportion of the respondent women (42.7%) were in the age group of 36-55 years with a mean age of 41±5 years and this analysis was found in agreement with the study conducted by Adelekan and Edoni 9 in Nigeria which reported that 65.3% respondents were in the age-group of 35-54 years with a mean age of 43.4 ± 9.2 years. It shows that both the studies have focused their study observations on the women around 40 years of age (nearing menopausal age) when the chances of development of breast cancer are comparatively higher 10 . Present study revealed that about 25% of the participants were illiterate.…”
Section: Discussionmentioning
confidence: 99%